Isolation, molecular identification and assessment of the biotechnological potential of yeasts from managed and forestry soils - Freitas, Fernanda Pinheiro Moreira (Universidade Federal de Viçosa, 2025)
The growing demand for bio-based products has boosted bioprospecting microorganisms capable of converting agro-industrial byproducts into high-value compounds. In this context, soil yeasts stand out for their metabolic versatility and biotechnological potential in the production of lipids and exopolysaccharides (EPS). In this study, we isolated and characterized yeasts from managed and forest soil samples, performing morphological grouping and PCR-fingerprinting to ensure genetic differentiation of the strains. In the first chapter, we selected both Candida maltosa UFV-1 and UFV-2 strains, which stood out for their ability to grow and accumulate lipids in culture media containing xylose as carbon source and acetic acid, the main inhibitor found in hemicellulosic hydrolysates. The yeasts also grew in culture media containing other inhibitors present in these hydrolysates such as furfural (4 g/L), hydroxymethylfurfural (4 g/L), and formic acid (0,5 g/L), indicating their potential for biorefinery processes with lignocellulosic biomasses. We applied a central composite rotational design (CCRD) with response surface methodology (RSM) to optimize growth and lipid production in non-detoxified malt bagasse hemicellulosic hydrolysate, evaluating initial pH (6.0–7.0) and different ratios of peptone:yeast extract (1:0–0:1 g/L). The predicted maximum conditions for C. maltosa UFV-1 were (P:YE = 1:0 g/L; pH = 6.0), whilst for C. maltosa UFV-2 were (P:YE = 0.58:0.42 g/L; pH = 6.5). Significant models for the lipid content and titers of were obtained for C. maltosa UFV-1, and lipid content for C. maltosa UFV-2. However, both strains did not achieve the predicted values in the non-detoxified hydrolysate. Detoxification significantly improved physiological parameters such as biomass, lipid content, lipid titer, lipid productivity, and lipid yield. The detoxification step allowed to increase the lipid content [UFV-1: 18.2% (w/w) and UFV-2: 12.2% (w/w)]. Importantly, we observed the production of ethanol (16.2-20.5 g/L) and glycerol (0.49-1.67 g/L) by both strains. Moreover, the fatty acid profile revealed that the most abundant acids were 16:0, 16:1, and 18:1, with an increase in saturated fatty acids 16:0, 18:0, and 10:0 in the detoxified media. These results demonstrate the potential of C. maltosa strains for biotechnological processes, demonstrating their robustness in growing and producing lipids under stress conditions, making them suitable for sustainable industrial processes. In the second chapter, we explored the potential of forest soil yeasts for EPS production, focusing on Cutaneotrichosporon sp. UFV-1, a strain selected for its pronounced mucoid phenotype on solid media containing sucrose, glucose, xylose and maltose (5% w/v) and growth in liquid media containing different carbon sources, especially lactose, glucose and galactose. Cutaneotrichosporon sp. UFV-1 showed the highest EPS production when grown with sucrose and lactose (concentrations close to 3.5 g/L). The EPS produced was characterized as a heteropolysaccharide, consisting of a mixture of mannose and fucose, with variations depending on the carbon source, including monomers of glucose, fructose, and galactose. This is the first experimental report demonstrating EPS production by a yeast of the genus Cutaneotrichosporon. These findings demonstrate the potential of yeasts to produce custom-made biopolymers, focusing on circular bioeconomy and sustainable processes. Keywords: circular bioeconomy; biopolymers; hemicellulosic hydrolysate; oleaginous yeasts; exopolysaccharides.

A crescente demanda por produtos de origem biológica tem impulsionado a bioprospecção de microrganismos capazes de converter subprodutos agroindustriais em compostos de alto valor agregado. Nesse contexto, as leveduras de solo se destacam por sua versatilidade metabólica e potencial biotecnológico na produção de lipídios e exopolissacarídeos (EPS). Neste estudo, isolamos e caracterizamos leveduras de amostras de solo manejado e florestal, realizando agrupamento morfológico e PCR-fingerprinting para garantir a diferenciação genética das linhagens. No primeiro capítulo, selecionamos as linhagens Candida maltosa UFV-1 e UFV-2, que se destacaram pela capacidade de crescer e acumular lipídios em meios de cultura contendo xilose como única fonte de carbono e ácido acético, principal inibidor encontrado em hidrolisados hemicelulósicos. As leveduras também cresceram em meios contendo outros inibidores presentes nesses hidrolisados, como furfural (4 g/L), hidroximetilfurfural (4 g/L) e ácido fórmico (0,5 g/L), indicando seu potencial para processos de biorrefinaria com biomassas lignocelulósicas. Aplicamos um delineamento composto central rotacional (DCCR) com metodologia de superfície de resposta (MSR) para otimizar o crescimento e a produção de lipídios em hidrolisado hemicelulósico de bagaço de malte não destoxificado, avaliando o pH inicial (6,0–7,0) e diferentes razões peptona:extrato de levedura (1:0–0:1 g/L). As condições máximas preditas para C. maltosa UFV-1 foram (P:YE = 1,0 g/L; pH = 6,0), enquanto para C. maltosa UFV-2 foram (P:YE = 0,58:0,43 g/L; pH = 6,5). Modelos significativos para o teor e título lipídico foram obtidos para C. maltosa UFV-1 e teor lipídico para UFV-2. No entanto, ambas as linhagens não alcançaram os valores preditos no hidrolisado não destoxificado. A destoxificação melhorou significativamente parâmetros fisiológicos como biomassa, teor de lipídios, título lipídico, produtividade lipídica e rendimento lipídico. A etapa de destoxificação permitiu o aumento do teor de lipídios [UFV-1: 18,2% (m/m) e UFV-2: 12,2% (m/m)]. Importante ressaltar que observamos a produção de etanol (16,2-20,5 g/L) e glicerol (0,49-1,67 g/L) por ambas as linhagens. Além disso, o perfil de ácidos graxos revelou que os mais abundantes foram 16:0, 16:1 e 18:1, com aumento dos ácidos graxos saturados 16:0, 18:0 e 10:0 no meio destoxificado. Esses resultados demonstram o potencial das linhagens de C. maltosa para processos biotecnológicos,evidenciando sua robustez em crescer e produzir lipídios sob condições de estresse, tornando-as adequadas para processos industriais sustentáveis. No segundo capítulo, exploramos o potencial de leveduras de solo florestal para a produção de EPS, com foco em Cutaneotrichosporon sp. UFV-1, uma linhagem selecionada por seu fenótipo mucoide pronunciado em meios sólidos contendo sacarose, glicose, xilose e maltose (5% m/v) e crescimento em meio líquido contendo diferentes fontes de carbono, especialmente, lactose, glicose e galactose. Cutaneotrichosporon sp. UFV-1 demonstrou maior produção de EPS quando cultivada com sacarose e lactose (concentrações próximas a 3,5 g/L). O EPS produzido foi caracterizado como um heteropolissacarídeo, composto por uma mistura de manose e fucose, com variações dependendo da fonte de carbono, incluindo monômeros de glicose, frutose e galactose. Este é o primeiro relato experimental demonstrando a produção de EPS por uma levedura do gênero Cutaneotrichosporon. Esses achados demonstram o potencial das leveduras na produção de biopolímeros sob medida, com foco na bioeconomia circular e em processos sustentáveis. Palavras-chave: bioeconomia circular; biopolímeros; hidrolisado hemicelulósico; leveduras oleaginosas; exopolissacarídeos.
Isolamento, identificação molecular e avaliação do potencial biotecnológico de leveduras de solos manejados e florestais
Keywords: Leveduras (Fungos); Biopolímeros; Lipídeos; Mapeamento cromossômico; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA INDUSTRIAL E DE FERMENTACAO